The Role of Civil Law in Realizing Personal Data Security in the Era of Digital Transformation in Indonesia - Piansah, Aip (Yayasan Mentari Madani, 2024)
This study discusses the role of civil law in realizing personal data security in Indonesia in the midst of the digital transformation era. With the rapid development of information technology, personal data has become very vulnerable to leakage and misuse, so legal protection is crucial. This study uses a normative juridical approach with a descriptive-analytical method to examine related laws and regulations, including the Civil Code (KUHPer) and the Personal Data Protection Law, as well as the challenges in their implementation. The results of the study show that although civil law provides an important legal framework, challenges such as lack of public awareness, suboptimal law enforcement, and complicated legal procedures hinder the effectiveness of personal data protection. Cases of personal data breaches reveal the potential for civil law mechanisms to provide protection, but they are often insufficient to effectively prevent breaches. Recommendations include increasing public awareness, strengthening law enforcement, simplifying legal procedures, and collaboration between the government, the private sector, and the public to strengthen personal data protection in Indonesia. This research is expected to provide insights and recommendations to improve personal data protection regulations in the digital era